Politics and morality in the career of alcibiades (2015)
The Greek historian, Thucydides, as well as the historian and biographer, Plutarch, are prominent sources of information about life and career of the Athenian politician and statesman, Alcibiades. While presenting the striking political contributions of Alcibiades as an orator, a military’ commander and a strategic adviser, the accounts of the duo also put on record some arguably ugly sides of his personality and offer parameters for examining how the activities of a politician become inimical to the interest of the state when the actions reflect his and societal foul values. Using qualitative interpretive method, this paper utilises Thucydides' The History of the Peloponnesian War and Plutarch's The Parallel Lives: The Life of Alcibiades to examine the political genius of Alcibiades and the moral questions it raised. Alcibiades' case is used to illustrate the impact of individual and societal values on political outcomes, especially when politicians resort to treachery and criminal acts to become the leaders of the people. Alcibiades's example, as discussed in the paper, also shows that the blame for political crisis would be shared between the electorate and the clever politician they elect to lead the state despite his failed character.